Impact of continuous glucose monitoring on glycemic control and its derived metrics in type 1 diabetes: a longitudinal study - Cho, So Hyun; Kim, Seohyun; Lee, You-Bin; Jin, Sang-Man; Hur, Kyu Yeon; Kim, Gyuri; Kim, Jae Hyeon (Frontiers in Endocrinology, 2023)
Aim: We explored the effectiveness of continuous glucose monitoring for one year on glycated A1c reduction in adults with type 1 diabetes mellitus. Methods: We included type 1 diabetes mellitus adults who were either new continuous glucose monitoring users (N=155) or non-users who were under standard care (N=384). Glycated A1c was measured at baseline and at three, six, nine, and 12 months. Individuals with (N=155) or without continuous glucose monitoring use (N=310) were matched 1:2 by propensity score. We used linear mixed models to identify the quantitative reduction in repeated measures of glycated A1c. Results: The change in glycated A1c from baseline to 12 months was -0.5 ± 1.0% for the continuous glucose monitoring user group (N=155, P<0.001) and -0.01 ± 1.0% for the non-user group (N=310, P=0.816), a significant difference between the two groups (P=0.003). Changes in glycated A1c were significant at three, six, nine, and 12 months compared to baseline in patients using continuous glucose monitoring (P<0.001), and the changes differed significantly between the groups (P<0.001). A linear mixed model showed an adjusted treatment-group difference in mean reduction in glycated A1c of -0.11% (95% confidence interval, -0.16 to -0.06) every three months. In the continuous glucose monitoring user group, those who achieved more than 70% of time in range significantly increased from three months (37.4%) to 12 months (48.2%) (P<0.001). Conclusion: In this longitudinal study of type 1 diabetes mellitus adults, use of continuous glucose monitoring for one year showed a significant reduction in glycated A1c in real-world practice.